Restorative Retelling for Processing Psychedelic Experiences: Rationale and Case Study of Complicated Grief - González, Débora; Aixalà, Marc B.; Neimeyer, Robert A.; Cantillo, Jordi; Nicolson, Donald; Farré, Magi (Frontiers in Psychology, 2022)
Rationale: Many psychedelic experiences are meaningful, but ineffable. Engaging in meaning-making regarding emerging symbolic content and changing previous schemas have been proposed as mechanisms of change in psychedelic therapy. Objective: Firstly, we suggest the implementation of a Restorative Retelling (RR) technique to process and integrate the psychedelic experience into autobiographical memory, in a way that fosters meaning-making. We also show how ayahuasca has the potential to evoke key psychological content in survivors, during the process of grief adjustment following the death of a loved one. Methods: The rationale for the implementation of RR to process psychedelic experiences and a case study of a woman suffering from Complicated Grief (CG) after her mother's suicide is​ presented. Results: Evaluations conducted before the ayahuasca experience and after RR suggest the effectiveness of ayahuasca and RR in reducing symptoms of CG and psychopathology. Conclusions: This case report illustrates an effective adaptation of the RR technique for processing the psychedelic experience. The significance of the study and its limitations are discussed.